The Influence of Human Resource Development on Inclusive Regional Economic Development: A Spatial Economic Assessment Approach - Rudy Mas’ud; Zamruddin Hasid; Rahcmad Budi Suharto; Diana Lestari (PT Inovasi Pratama Internasional, 2024)
Economics is treated effectively by standard economics. In spatial economics, the interaction between Agglomeration Forces, which attract economic activity to a particular region, and Dispersion Forces, which spread economic activity throughout the surrounding region, determines the geographic distribution of economic activity. Spatial Economic Analysis will provide an understanding of how space (distance) influences economic behavior referring to each type of economic entity. The method used in this research is a quantitative research method. Multivariate analysis is used in analyzing research, involving variables in a number more than or equal to three variables. The method used in this research is a quantitative research method. Multivariate analysis is used in analyzing research, involving variables in a number more than or equal to three variables. Development policies must be tailored to specific regions to encourage local production and innovative networks and make the manufacturing industry more competitive. The populations of most cities in urban agglomerations are still spread out. Although urban populations tend to cluster around a few sub-central urban units, the trend is toward population agglomeration around urban centers. The decline in technological progress and technological efficiency will affect the spatial structure of urban agglomeration and influence economic efficiency.